Financial Literacy and House Hold Portofolio Diversification: The Moderation Role of Risk Preferences - Shelfi Malinda; Mu'izzuddin Mu'izzuddin; Febri Marani Malinda; Kharisya Ayu Effendi (AFRE (Accounting and Financial Review), 2024)
The study examines the relationship between financial literacy and household portfolio diversification in Palembang, Indonesia. The sample was proportio-nally surveyed using proportional random sampling, so 405 households in Palembang, Indonesia divided into 18 districts. Inferential testing uses Struc-tural Equation Modeling (SEM) based on variants, namely Partial Least Squ-are (SEM-PLS). Results show that financial literacy positively influences port-folio diversification, while risk preference moderates this effect. The interaction between financial literacy and risk preference has a smaller effect size. The stu-dy contributes to the concept of optimal portfolios in Modern Portfolio Theory, as financial literacy encourages logical decisions and risk preferences optimize diversification decisions. The study also found that risk preference reduces the effect of financial literacy on portfolio diversification, as households understand that additional asset distribution may increase costs and reduce returns. Re-search suggests incorporating risk preference as a predictor and mediator to better understand the impact of financial literacy on portfolio diversification.DOI: https://doi.org/10.26905/afr.v7i2.12437